Phylogeography and species delimitation in convict cichlids (Cichlidae: Amatitlania): implications for taxonomy and Plio-Pleistocene evolutionary history in Central America - Bagley, Justin C.; Matamoros, Wilfredo A.; McMahan, Caleb D.; Tobler, Michael; Chakrabarty, Prosanta; Johnson, Jerald B. (Wiley-Blackwell, 2017)
We investigate phylogeographic patterns and delimit species boundaries within Amatitlania, a genus of Central American cichlid fishes. Phylogenetic analyses of mitochondrial DNA sequences from 318 individuals spanning the geographical ranges of all three currently recognized Amatitlania species strongly supported one major clade, with a relatively diverged subclade corresponding to A. kanna samples from eastern Costa Rica and Panama. Gene trees and networks revealed marked incongruences between phylogeographic structure and morpho-species taxonomy as a result of species-level polyphyly. Bayes factor comparisons of species delimitation models accounting for incomplete lineage sorting under the multispecies coalescent decisively supported the recognition of two distinct species within Amatitlania corresponding to Amatitlania nigrofasciata and A. kanna lineages. The only clearly genetically and morphologically diagnosable species was A. kanna. These results strongly suggest that incomplete lineage sorting provides the best explanation for the polyphyly of A. kanna, whereas the polyphyly of A. siquia is likely a result of an imperfect taxonomy. Additional insights from coalescent-dating, network, and historical demographic analyses suggested that the two species of Amatitlania diversified only since the early Pleistocene, and that A. nigrofasciata experienced population expansions from approximately 200 000 years ago in the mid-late Pleistocene onward. We discuss implications of our results for the taxonomy and evolutionary history of Amatitlania and, more broadly, of Central American freshwater fishes. (C) 2016 The Linnean Society of London
Keywords: BEAST; Bayes factor delimitation; freshwater fishes; historical demography; mitochondrial DNA; model comparison; species trees; taxonomy